Analysis the Validity of Realistic Mathematics Education (RME) Learning Module on Integers Operations for Grade VII - Dianti, Zulfa; Irawan, Dody; Nevrita, Nevrita; Zaitun, Zaitun (Universitas Negeri Makassar, 2025)
This study aims to describe validity level of mathematics learning module based on Realistic Mathematics Education (RME) on topic of integer operations for seventh-grade students. This research is part of Research and Development study using ADDIE model, which consist the stages of Analysis, Design, Development, Implementation, and Evaluation. However, this article focuses only on Development stage, specifically the product validity test by experts. The validation subjects included six validators divided into three expert groups, namely two material experts, two language experts, and two media experts. The instrument used was validation sheet covering four aspects: content feasibility, language, presentation, and graphics. The data were analyzed quantitatively based one the percentage of validation results. The findings showed that module achieved average validity score of 88,50% (very valid), consisting of 89,5% for content, 91% for language, and 85% for media aspects. Thus, RME-based mathematics module developed in this study meets validity criteria and is suitable for classroom implementation.